Resource utilization method of retired wind turbine blade and thermal insulation material

By cutting, crushing, mixing and freeze-drying the blades of the retired wind turbine, fiberglass-sodium alginate composite aerogel insulation material was prepared, which solved the problem of environmental pollution caused by the recycling and utilization of the retired wind turbine blades, and achieved efficient resource utilization and improved thermal insulation performance.

CN119874240AActive Publication Date: 2025-04-25XIAN THERMAL POWER RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510145507.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-25
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The existing methods of recycling and utilization of retired wind turbine blades have serious environmental pollution and lack effective resource utilization methods.

Method used

By cutting and crushing the blade materials of the retired wind turbine, mixing them with sodium alginate and sodium hyaluronate after screening, calcium compounds and crosslinking agents are added, and then ultrasonic crushing and freeze-drying are processed to prepare fiberglass-sodium alginate composite aerogel thermal insulation material.

Benefits of technology

The resource utilization of retired wind turbine blades has been realized, environmental pollution has been reduced, and high-performance insulation materials have been prepared, with extremely low density, high porosity and excellent thermal insulation performance, and are suitable for construction, transportation, aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874240A_ABST
    Figure CN119874240A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of wind turbine blade recycling, and discloses a resource utilization method and a heat insulation material of an out-of-service wind turbine blade, and the method comprises the following steps: cutting, crushing and screening an out-of-service wind turbine blade material to obtain a blade glass fiber reinforced plastic waste crushed material; dispersing the crushed blade glass fiber reinforced plastic waste into water, and carrying out ultrasonic crushing treatment to obtain glass fiber reinforced plastic dispersion liquid; mixing the sodium alginate / sodium hyaluronate mixed solution with the glass fiber reinforced plastic dispersion liquid to obtain a mixed dispersion liquid; adding a calcium compound into the mixed dispersion liquid, and stirring until the calcium compound is uniformly dispersed to obtain a uniform dispersion liquid; adding a cross-linking agent into the uniform dispersion liquid, and standing for cross-linking until gelation is completely realized to obtain a gelation product; and freeze-drying the gelatinized product to obtain the glass fiber reinforced plastic-sodium alginate composite aerogel thermal insulation material. Effective conversion of the retired wind turbine blades and cyclic utilization of resources are achieved, and environmental pollution caused by recycling of the wind turbine blades is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wind turbine blade recycling and reuse, and in particular relates to a resource utilization method and a heat insulation material for retired wind turbine blades. Background Art

[0002] With the continuous development of the wind power industry, the scale of wind turbines and wind turbine blades has continued to increase; with the expiration of the service life of wind turbines, the number of retired wind turbines and wind turbine blades that need to be processed in the future will also continue to increase dramatically; therefore, the recycling and utilization of retired wind turbine blades is a key issue that needs to be urgently resolved in the wind power industry.

[0003] The main material of wind turbine blades is fiberglass, that is, epoxy resin and glass fiber composite material; currently, the reuse methods for retired wind turbine blades mainly include direct recycling, energy recycling and reprocessing as building materials; among them, direct recycling is to crush or cut the blades into small pieces, and then subject them to chemical or physical treatment to extract the glass fiber and resin for the manufacture of new composite products; energy recycling is to use retired blades as fuel and convert them into energy, such as heat or combustible gas, through pyrolysis or gasification processes; reprocessing as building materials is to process blade materials into building materials, such as concrete reinforcement materials or as part of building structures; however, the above-mentioned existing recycling methods generally cause serious pollution to the environment. Faced with a large number of retired wind turbine blades in the future, we continue to look for zero-waste recycling methods. Summary of the invention

[0004] In view of the technical problems existing in the prior art, the present invention provides a resource utilization method and thermal insulation material for retired wind turbine blades to solve the technical problem of serious environmental pollution commonly found in the existing wind turbine blade recycling methods.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for resource utilization of retired wind turbine blades, comprising: Cut, crush and screen the retired wind turbine blade materials to obtain blade fiberglass waste fragments; Dispersing blade fiberglass waste material into water, and subjecting it to ultrasonic crushing treatment to obtain fiberglass dispersion liquid; Mixing the sodium alginate / sodium hyaluronate mixed solution with the glass fiber reinforced plastic dispersion to obtain a mixed dispersion; Adding calcium compounds to the mixed dispersion, stirring until uniform dispersion is obtained to obtain a uniform dispersion; Adding a cross-linking agent to the uniform dispersion, allowing the dispersion to stand for cross-linking until gelation is completely achieved, thereby obtaining a gelled product; The gelled product is freeze-dried to obtain a glass fiber reinforced plastic-sodium alginate composite aerogel thermal insulation material.

[0006] Furthermore, the particle size of the blade FRP waste material is greater than 50 meshes; and the particle size of the blade FRP waste material in the FRP dispersion is 10-100 μm.

[0007] Furthermore, the blade fiberglass waste material fragments are dispersed in water and ultrasonically crushed to obtain the fiberglass dispersion liquid, and an ultrasonic crusher is used for ultrasonic crushing treatment.

[0008] Furthermore, the mass ratio of sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion is (2-4):1:(10-12).

[0009] Furthermore, in the process of adding the calcium compound to the mixed dispersion, the amount of the calcium compound added is 1%-3% of the total mass of the sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion.

[0010] Furthermore, the calcium compound is one of calcium carbonate, calcium chloride and calcium sulfate.

[0011] Furthermore, the cross-linking agent is D-gluconolactone.

[0012] Furthermore, a crosslinking agent is added to the uniform dispersion, and the crosslinking is allowed to stand for 30-600 minutes at 25-60° C. to obtain a gelled product.

[0013] Furthermore, the gelled product is freeze-dried to obtain the FRP-sodium alginate composite aerogel insulation material, and the freeze-drying temperature is -40~-80°C and the time is 24-120h.

[0014] The present invention also provides a thermal insulation material, which is a glass fiber reinforced plastic-sodium alginate composite aerogel thermal insulation material; the glass fiber reinforced plastic-sodium alginate composite aerogel thermal insulation material is prepared by adopting the resource utilization method of retired wind turbine blades.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The resource utilization method of retired wind turbine blades provided by the present invention uses retired wind turbine blade materials as raw materials, adds sodium alginate and sodium hyaluronate, and uses freeze-drying technology to obtain glass fiber reinforced plastic-sodium alginate composite aerogel insulation material, so as to convert the discarded blades into high-performance insulation materials, thereby achieving effective conversion of retired wind turbine blades and recycling of resources, and effectively reducing the pollution to the environment caused by the recycling of wind turbine blades; the composite aerogel insulation material has extremely low density, high porosity and excellent thermal insulation performance, so that the material can effectively block heat transfer while maintaining light weight, so that the composite aerogel material has potential application advantages in the field of thermal insulation; wherein, by adding calcium compounds and cross-linking agents, gelation of the mixed dispersion is achieved, the process method is simple and easy to operate, and the structure and performance of the material can be effectively controlled. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 This is a scanning electron microscope image of the fiberglass scraps of the blade in Example 1; Figure 2 This is a scanning electron microscope image of the glass fiber reinforced plastic-sodium alginate composite aerogel insulation material in Example 1 at 200 μm; Figure 3 This is a scanning electron microscope image of the fiberglass-sodium alginate composite aerogel insulation material in Example 1 at 10 μm. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely in combination with the drawings in the embodiments of this application; obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] The present invention provides a method for resource utilization of retired wind turbine blades, comprising the following steps: Step 1: Physically cut and crush the retired wind turbine blade materials, and screen the crushed fiberglass waste to obtain blade fiberglass waste fragments; wherein the particle size of the blade fiberglass waste fragments is greater than 50 meshes.

[0020] Step 2: Disperse the blade FRP waste fragments into distilled water, and crush them using an ultrasonic crusher to obtain a FRP dispersion; wherein the particle size of the blade FRP waste fragments in the FRP dispersion is 10-100 μm.

[0021] Step 3, dissolving sodium alginate and sodium hyaluronate in distilled water to obtain a sodium alginate / sodium hyaluronate mixed solution; mixing the sodium alginate / sodium hyaluronate mixed solution with a glass fiber reinforced plastic dispersion to obtain a mixed dispersion; wherein the mass ratio of sodium alginate, sodium hyaluronate and glass fiber reinforced plastic in the mixed dispersion is (2-4):1:(10-12).

[0022] Step 4: Add a calcium compound to the mixed dispersion and stir until it is evenly dispersed to obtain a uniform dispersion; wherein the amount of calcium carbonate powder added is 1%-3% of the total mass of sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion; the calcium compound is one of calcium carbonate, calcium chloride and calcium sulfate. Step 5: adding a crosslinking agent to the uniform dispersion, standing and crosslinking for 30-600 minutes at 25-60° C. to obtain a gelled product; wherein the crosslinking agent is D-gluconolactone.

[0023] Step 6: freeze-dry the gelled product to obtain a glass fiber reinforced plastic-sodium alginate composite aerogel insulation material; wherein the freeze-drying temperature is -40 to -80°C and the time is 24 to 120 hours.

[0024] Principles of resource utilization method: The resource utilization method of retired wind turbine blades described in the present invention effectively reduces the generation of waste and reduces the burden on the environment by recycling retired wind turbine blades; converts the discarded blades into new thermal insulation materials, realizes the recycling of resources and improves the utilization efficiency of resources; specifically, the waste glass fiber reinforced plastics are crushed by ultrasound, which improves the dispersibility of the waste and provides favorable conditions for the subsequent preparation of a uniform dispersion liquid; the waste glass fiber reinforced plastics are used as the reinforcing phase of the thermal insulation material, which not only significantly improves the mechanical strength of the thermal insulation material, but also has good thermal insulation performance; by adding sodium alginate and sodium hyaluronate, the molding of the waste glass fiber reinforced plastics is enhanced, so that it has good thermal insulation performance; by adding calcium compounds and cross-linking agents, the gelation of the mixed dispersion is realized, and the structure and performance of the material can be effectively controlled; the present invention realizes the resource utilization of retired wind turbine blades, without the need to separate or transform the waste glass fiber reinforced plastics, without generating additional waste, and the waste is fully utilized through physical, chemical and physicochemical processes to form a glass fiber reinforced plastic-sodium alginate composite aerogel thermal insulation material with high added value, which has potential application value in high-performance thermal insulation materials.

[0025] In the present invention, retired wind turbine blade materials are used as raw materials, sodium alginate and sodium hyaluronate are added, and a glass fiber reinforced plastic-sodium alginate composite aerogel insulation material is obtained by freeze-drying technology, so as to convert the discarded blades into high-performance insulation materials, thereby realizing the effective conversion of retired wind turbine blades and the recycling of resources, and effectively reducing the pollution to the environment caused by the recycling of wind turbine blades; the composite aerogel insulation material has extremely low density, high porosity and excellent thermal insulation performance, so that the material can effectively block heat transfer while maintaining light weight, so that the composite aerogel material has potential application advantages in the field of thermal insulation; wherein, by adding calcium compounds and cross-linking agents, the gelation of the mixed dispersion is realized, the process method is simple and easy to operate, and the structure and performance of the material can be effectively controlled.

[0026] Example 1 This embodiment 1 provides a method for resource utilization of retired wind turbine blades, including the following steps: Step 1: Place the retired wind turbine blade material in a high-speed crusher for physical cutting, and use a ball mill to crush it to obtain the crushed material; use a 50-mesh standard test sieve to sieve the crushed material to obtain blade fiberglass waste fragments with a particle size greater than 50 mesh.

[0027] Step 2: Disperse 5 g of blade FRP waste fragments into 30 mL of distilled water, and crush them using an ultrasonic crusher for 2 hours to obtain a FRP dispersion; wherein the particle size of the blade FRP waste fragments in the FRP dispersion is 10-100 μm.

[0028] Step 3: dissolve 1.4 g of sodium alginate and 0.44 g of sodium hyaluronate in 75 mL of distilled water to obtain a sodium alginate / sodium hyaluronate mixed solution; mix the sodium alginate / sodium hyaluronate mixed solution with the fiberglass dispersion to obtain a mixed dispersion.

[0029] Step 4: Add 0.2 g of calcium carbonate powder to the mixed dispersion and stir at room temperature until the mixture is evenly dispersed to obtain a uniform dispersion.

[0030] Step 5: Add 0.06 mL of D-gluconolactone to the uniform dispersion, and allow to stand for crosslinking at 60° C. for 30 minutes to obtain a gelled product.

[0031] Step 6: freeze-dry the gelled product at a freeze-drying temperature of -40°C for 120 hours to obtain a fiberglass-sodium alginate composite aerogel insulation material.

[0032] As attached Figure 1 As shown, attached Figure 1The scanning electron microscope image of the fiberglass scraps of the blade in Example 1 is given in FIG. Figure 1 It can be seen that the blade FRP waste fragments present a typical fiber and debris structure, and there are irregular debris particles on the fiber surface.

[0033] As attached Figure 2-3 As shown, attached Figure 2 The scanning electron microscope image of the glass fiber reinforced plastic-sodium alginate composite aerogel insulation material in Example 1 at 200 μm is given in the attached Figure 3 The scanning electron microscope image of the glass fiber reinforced plastic-sodium alginate composite aerogel insulation material in Example 1 at 10 μm is given in the attached figure. Figure 2-3 It can be seen that by adding FRP, the FRP-sodium alginate composite aerogel insulation material retains the original porous network structure, and its pore wall is very rough; among them, the typical rod-shaped glass fibers are staggered in the aerogel matrix as a skeleton; the FRP obtained after mechanical crushing of retired blades is a rod-shaped fiber structure with uneven length. These fibers are very richly distributed on the pore wall and embedded in the pore wall like a brick and mud structure; the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled.

[0034] Performance test results description: The FRP-sodium alginate composite aerogel thermal insulation material prepared in this Example 1 was tested, and the test results were as follows: under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel thermal insulation material reached 1 MPa; wherein, the FRP scraps were used as a reinforcing phase material to support the thermal insulation composite material's resistance to pressure, and the compressive strength was increased by more than two times; the thermal conductivity of the FRP-sodium alginate composite aerogel thermal insulation material was only 0.041 W / (m∙K), indicating its excellent thermal insulation performance.

[0035] Example 2 The method for resource utilization of retired wind turbine blades provided in this embodiment 2 is basically the same as the method process of the above embodiment 1, except that: In the mixed dispersion of step 3, the mass ratio of sodium alginate, sodium hyaluronate and fiberglass is 2:1:10; the remaining steps are basically the same and will not be repeated here.

[0036] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.1 MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.040 W / (m∙K).

[0037] Example 3 The method for resource utilization of retired wind turbine blades provided in this embodiment 3 is basically the same as the method process of the above embodiment 1, except that: In the mixed dispersion of step 3, the mass ratio of sodium alginate, sodium hyaluronate and fiberglass is 3:1:12; the remaining steps are basically the same and will not be repeated here.

[0038] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.02 MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.042W / (m∙K).

[0039] Example 4 The method for resource utilization of retired wind turbine blades provided in this embodiment 4 is basically the same as the method process of the above embodiment 1, except that: In the mixed dispersion of step 3, the mass ratio of sodium alginate, sodium hyaluronate and fiberglass is 4:1:11; the remaining steps are basically the same and will not be repeated here.

[0040] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.4MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.039W / (m∙K).

[0041] Example 5 The method for resource utilization of retired wind turbine blades provided in this embodiment 5 is basically the same as the method process of the above embodiment 1, except that: In step 4, the calcium compound added is calcium chloride, and the amount of calcium chloride added is 1% of the total mass of sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion.

[0042] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel thermal insulation material reaches 0.99MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the thermal insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel thermal insulation material is only 0.043W / (m∙K).

[0043] Example 6 The method for resource utilization of retired wind turbine blades provided in this embodiment 6 is basically the same as the method process of the above embodiment 1, except that: In step 4, the calcium compound added is calcium sulfate, and the amount of calcium chloride added is 2% of the total mass of sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion.

[0044] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel thermal insulation material reaches 0.93MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the thermal insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel thermal insulation material is only 0.048W / (m∙K).

[0045] Example 7 The method for resource utilization of retired wind turbine blades provided in this embodiment 7 is basically the same as the method process of the above embodiment 1, except that: In step 5, a crosslinking agent is added to the uniform dispersion, and the mixture is allowed to stand for crosslinking until gelation is completely achieved. In the process of obtaining a gelled product, the crosslinking is performed at 35° C. for 400 minutes.

[0046] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.2MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.040W / (m∙K).

[0047] Example 8 The method for resource utilization of retired wind turbine blades provided in this embodiment 8 is basically the same as the method process of the above embodiment 1, except that: In step 5, a crosslinking agent is added to the uniform dispersion, and the mixture is allowed to stand for crosslinking until gelation is completely achieved. In the process of obtaining a gelled product, the crosslinking is performed at 25° C. for 600 minutes.

[0048] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.11 MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.043W / (m∙K).

[0049] Example 9 The method for resource utilization of retired wind turbine blades provided in this embodiment 9 is basically the same as the method process of the above embodiment 1, except that: In step 6, the freeze-drying temperature is -50°C and the time is 60 hours.

[0050] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.05 MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.041W / (m∙K).

[0051] Example 10 The method for resource utilization of retired wind turbine blades provided in this embodiment 10 is basically the same as the method process of the above embodiment 1, except that: In step 6, the freeze-drying temperature is -80°C and the time is 24 minutes.

[0052] Performance test results description: Under a compressive strain of 71%, the compressive strength of the FRP-sodium alginate composite aerogel insulation material reaches 1.01 MPa; wherein, the FRP scraps are used as a reinforcing phase material to support the insulation composite material's resistance to pressure, and the compressive strength is more than doubled; the thermal conductivity of the FRP-sodium alginate composite aerogel insulation material is only 0.044W / (m∙K).

[0053] The resource utilization method of retired wind turbine blades described in the present invention mixes FRP waste with sodium alginate / sodium hyaluronate, and combines the treatment with calcium compounds and cross-linking agents to prepare a composite aerogel material with excellent thermal insulation performance. The raw materials used are mainly retired wind turbine blades and two natural polymer materials, sodium alginate and sodium hyaluronate. No toxic and harmful chemicals are used in the preparation process, so the impact on the environment is small, so that FRP waste can be effectively converted and utilized; the prepared FRP-sodium alginate composite aerogel insulation material has broad application prospects in the fields of construction, transportation, aerospace, etc.; among them, the application of ultrasonic crushing and freeze-drying technology helps to obtain a more uniform and delicate material structure.

[0054] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.

Claims

1. A method for resource utilization of retired wind turbine blades, characterized in that: include: Cut, crush and screen the retired wind turbine blade materials to obtain blade fiberglass waste fragments; Dispersing blade fiberglass waste material into water, and subjecting it to ultrasonic crushing treatment to obtain fiberglass dispersion liquid; Mixing the sodium alginate / sodium hyaluronate mixed solution with the glass fiber reinforced plastic dispersion to obtain a mixed dispersion; Adding calcium compounds to the mixed dispersion, stirring until uniform dispersion is obtained to obtain a uniform dispersion; Adding a cross-linking agent to the uniform dispersion, allowing the dispersion to stand for cross-linking until gelation is completely achieved, thereby obtaining a gelled product; The gelled product is freeze-dried to obtain a glass fiber reinforced plastic-sodium alginate composite aerogel thermal insulation material.

2. A method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: The particle size of the blade fiberglass waste material is greater than 50-300 meshes; the particle size of the blade fiberglass waste material in the fiberglass dispersion is 10-100 μm.

3. The method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: The scraps of blade fiberglass reinforced plastics are dispersed in water and ultrasonically crushed to obtain a fiberglass reinforced plastic dispersion, and an ultrasonic crusher is used for ultrasonic crushing.

4. The method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: The mass ratio of sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion is (2-4):1:(10-12).

5. The method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: In the process of adding the calcium compound into the mixed dispersion, the amount of the calcium compound added is 1%-3% of the total mass of the sodium alginate, sodium hyaluronate and fiberglass in the mixed dispersion.

6. A method for resource utilization of retired wind turbine blades according to claim 5, characterized in that: The calcium compound is one of calcium carbonate, calcium chloride and calcium sulfate.

7. The method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: The crosslinking agent is D-gluconolactone.

8. The method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: A crosslinking agent is added to the uniform dispersion, and the crosslinking is allowed to stand for 30-600 minutes at 25-60° C. to obtain a gelled product.

9. The method for resource utilization of retired wind turbine blades according to claim 1, characterized in that: The gelled product is freeze-dried to obtain the FRP-sodium alginate composite aerogel insulation material, with the freeze-drying temperature being -40 to -80°C and the time being 24 to 120 hours.

10. A heat insulating material, characterized in that: The thermal insulation material is a fiberglass-sodium alginate composite aerogel thermal insulation material; the fiberglass-sodium alginate composite aerogel thermal insulation material is prepared by the resource utilization method of retired wind turbine blades as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-elasticity anti-cracking glass wool felt

    CN110451850A

  • Waste glass fiber reinforced plastic wind power blade recovery production line and recovery method thereof

    CN115716346A

  • Preparation method of reduced graphene oxide-chopped carbon fiber reinforced carbon-based composite material

    CN118206389A

  • Inorganic degradable plastic masterbatch material, and preparation method therefor

    US20220195131A1

  • Nanometer hydroxyapatite / natural polymer composite material, preparation method and use thereof

    WO2011035573A1